Polaritons in Non‐Fullerene Acceptors for High Responsivity Angle‐Independent Organic Narrowband Infrared Photodiodes - Abdelmagid, Ahmed Gaber; Qiao, Zhuoran; Coenegracht, Boudewijn; Yu, Gaon; Qureshi, Hassan A.; Anthopoulos, Thomas D.; Gasparini, Nicola; Daskalakis, Konstantinos S. (Wiley, 2026)
Narrowband infrared organic photodetectors are in great demand for sensing, imaging, and spectroscopy applications, in particular for handheld and wearable devices, in which miniaturization is essential. However, most existing strategies for narrowband detection depend on spectral filtering either through saturable absorption, which requires active layers exceeding 500 nm, restricting the choice of materials for producing high-quality films, or cavity effects, which inherently introduce strong angular dispersion. Microcavity exciton-polariton (polariton) modes, which emerge from strong exciton-photon coupling, have recently been explored as an angular dispersion suppression strategy for organic optoelectronics. In this work, the first narrowband infrared polariton organic photodiode that combines angle-independent response with a record-high responsivity of 0.24 A W-1 at 965 nm and -2 V is presented. This device, featuring a 100-nm-thin active layer comprising a non-fullerene acceptor, exhibits a detection mode with a full-width at half-maximum of less than 30 nm and a marginal angular dispersion of under 15 nm across +/- 45 degrees. This study highlights the potential of polaritons as an innovative platform for developing next-generation optoelectronic devices that achieve simultaneous enhancements in optical and electronic performance.